Impact of methane emission and associated environmental stress on livestock production systems in India - Biswal, J.; Kennady, Vijayalakshmy; Rahman, Habibar (2020)
Livestock farming in India is one of the significant anthropogenic sources of methane (CH4) emission. The present study as an effort to review and analyze the present status of methane emission by the Indian livestock. The anaerobic conditions of the large fore stomach of the rumen lead to release of methane as a by-product from the digestive system, which shares about 90% of the methane contributed by livestock, with other 10% generated through reaction from manure heaps. The impact of the climate change on the livestock productivity, breeding performance and disease threats has also been highlighted.